Say No to Success—Say Yes to Goal Setting. Issue 4 (July 2017) - Spatz, Diane L.
Abstract : The choice of words in promoting breastfeeding is very important. Our breastfeeding expert, Dr. Spatz, urges us to consider eliminating "success" from discussions with new mothers who are breastfeeding, and to focus instead on providing realistic information about the potential challenges and the investment in time and effort that is required, and helping them set short-term, mid-term and long term breastfeeding goals.